Hubungan Antara Pengetahuan Dengan Akses Kesehatan Reproduksi Remaja Di SMAN 1 Colomadu - Vina Apriliana; Faizah Betty Rahayuningsih (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Background: This study highlights the importance of knowledge and information access regarding reproductive health in adolescents, as adolescence is a transitional period susceptible to significant physical, emotional, and social changes. Survey data indicate that the level of reproductive health knowledge among Indonesian adolescents remains low, and access to information is very limited, especially from educational institutions. Objective: The objective of this study is to analyze the relationship between adolescent knowledge levels and access to reproductive health information at SMA Negeri Colomadu. Methods: This study utilizes a quantitative design with a cross-sectional approach. The sample consists of 72 respondents who meet the inclusion criteria with urposive sampling. The research instrument was a questionnaire measuring demographic characteristics, knowledge levels, and access to reproductive health information. A pre-post test data collection technique was applied to assess changes in knowledge following a health information intervention. Results: Bivariate analysis results showed a moderate positive correlation between access to information and reproductive health knowledge, with a Pearson coefficient of 0.550 (p < 0.01). Conclusion: This study demonstrates a significant relationship between information access and reproductive health knowledge among adolescents, where better information access supports improved understanding of reproductive health.